Delamanid and bedaquiline to treat multidrug-resistant and extensively drug-resistant tuberculosis in children: a systematic review - D’Ambrosio, Lia; Centis, Rosella; Tiberi, Simon; Tadolini, Marina; Dalcolmo, Margareth; Rendon, Adrian; Esposito, Susanna; Migliori, Giovanni Battista (Journal of Thoracic Disease, 2017)
The new drugs delamanid and bedaquiline are increasingly used to treat multidrug-resistant (MDR-) and extensively drug-resistant tuberculosis (XDR-TB). As evidence is lacking, the World Health Organization recommends their use under specific conditions in adults, delamanid only being recommended in children ≥6 years of age. No systematic review has yet evaluated the efficacy, safety and tolerability of the new drugs in children. A search of peer-reviewed, scientific evidence was performed, to evaluate the efficacy/effectiveness, safety, and tolerability of delamanid or bedaquiline-containing regimens in children with confirmed M/XDR-TB. We used PubMed and Embase to identify any relevant manuscripts in English until 31 December 2016, excluding editorials and reviews. Three out of 96 manuscripts retrieved satisfied the inclusion criteria, while 93 were excluded because dealing exclusively with adults (12: 4 on delamanid and 8 on bedaquiline), being recommendations or guidelines (8 manuscripts), reviews (17 papers) or other studies (56 papers). One of the studies retrieved reported evidence on 19 M/XDR-TB children, 16 of them treated under compassionate use with delamanid (13 achieving consistent bacteriological conversion) and 3 candidates for the drug. Two studies reported details on the first paediatric case treated (and cured) with a delamanid-containing regimen. Eight trials including children were also retrieved (clinicaltrials.gov). Although the methodology used in the study was rigorous, the results are limited by the paucity of the studies available in the literature on the use of new anti-TB drugs in children. In conclusion, more evidence is needed on the use of delamanid and bedaquiline in paediatric patients.